Illness, Taboo, and Autobiography. Mask Games and the Like in Mr. Parkinson by Richard Wagner - LEIPELT-TSAI, Monika (Anafora, 2023)
Following the turn of the millennium, the previously tabooed topic of "neurodegenerative diseases," which indicates a global demographic change, is particularly popular through dementia narratives in German-language literature. Richard Wagner prominently thematizes the second most common neurodegenerative disease, Parkinson’s disease, in his book Mr. Parkinson (2015). He addresses the illness for the first time from the perspective of an afflicted person and breaks with the convention of literary discourse. Wagner addresses different phases of the disease, from diagnosis to the failure of controlling the musculoskeletal system. His narrative technique uses a variety of sophisticated linguistic games that require a closer examination. This opens up questions: why were diseases such as Parkinson’s previously considered taboo? How are autobiography and fiction intertwined? What poetological reflection is referred to in Mr. Parkinson? Wagner’s text performatively stages the possibility and impossibility of speaking as a person with Parkinson’s disease. Games appear as a motif, in the process of language play and allusion, and in the complex entanglement of a mask game that unfolds symptoms of the disease as split consciousness. Parkinson’s disease seems to produce surreal anachronistic hallucinations, and thus questions the identity of the self.